Association of dementia and patient outcomes among COVID-19 patients: A multi-center retrospective case-control study - Vekaria, Pratikkumar H.; Syed, Areej; Anderson, Jeffrey; Cornett, Brendon; Bourbia, Amine; Flynn, Michael G.; Kashyap, Rahul; Shah, Asif R. (Frontiers in Medicine, 2022)
Background: We conducted a retrospective cohort study on COVID-19 patients with and without dementia by extracting data from the HCA Healthcare Enterprise Data Warehouse between January-September 2020. Aims: To describe the role of patients' baseline characteristics specifically dementia in determining overall health outcomes in COVID-19 patients. Methods: We grouped in-patients who had ICD-10 codes for dementia (DM) with age and gender-matched (1:2) patients without dementia (ND). Our primary outcome variables were in-hospital mortality, length of stay, Intensive Care Unit (ICU) admission, ICU-free days, mechanical ventilation (MV) use, MV-free days and 90-day re-admission. Results: Matching provided similar age and sex in DM and ND groups. BMI (median, 25.8 vs. 27.6) and proportion of patients who had smoked (23.3% vs. 31.3%) were lower in DM than in ND patients. The median (IQR) Elixhauser Comorbidity Index was higher in dementia patients 7 (5-10) vs. 5 (3-7, p < 0.01). Higher mortality was observed in DM group (30.8%) vs. ND group (26.4%, p < 0.01) as an unadjusted univariate analysis. The 90-day readmission was not different (32.1% vs. 31.8%, p=0.8). In logistic regression analysis, the odds of dying were not different between patients in DM and ND groups (OR=1.0; 95% CI 0.86-1.17), but the odds of ICU admissions were significantly lower for dementia patients (OR=0.58, 95% CI 0.51-0.66). Conclusions: Our data showed that COVID-19 patients with dementia did not fare substantially worse, but in fact, fared better when certain metrics were considered.